Bedside Procedures in the ICU - Falter, Florian (Springer London : Imprint: Springer, 2012)
At often critical times, ICU staff require immediate access to information regarding the management of patients in terms of procedures, drugs or any other aspect of treatment. Written by experts in the field of ICU, Bedside Procedures in the ICU facilitates rapid acquiring of clinical knowledge in a concise and didactic format. Focusing on the most commonly performed procedures in the Intensive Care Unit, this book examines 20 procedures all the way from indication to the management of possible complications. This easy to follow guide provides practical advice and essential background for every member of the multi-disciplinary team caring for critically ill patients, from the senior practitioner who has not performed a procedure for some time, to the junior doctor in need of step by step guidance.